Large‐for‐gestational age diagnosed during second‐trimester anatomy ultrasound and association with gestational diabetes and large‐for‐gestational age at birth. (1st December 2020) - Rekawek, P.; Liu, L.; Getrajdman, C.; Brooks, C.; Pan, S.; Overbey, J.; Wagner, B.
ABSTRACT: Objectives: To determine if large‐for‐gestational age (LGA) diagnosed during second‐trimester ultrasound examination is associated with the development of gestational diabetes mellitus (GDM) and LGA at birth. Methods: This was a retrospective cohort study of all pregnant women who underwent a second‐trimester anatomy ultrasound examination between 18 and 22 weeks at our institution from 2012 to 2017. Patients were included in the LGA group if estimated fetal weight and/or fetal abdominal circumference was ≥ 90 th percentile for gestational age. Patients with a history of pre‐GDM, multiple gestation, preterm delivery, use of betamethasone or fetal anomaly were excluded. The control group consisted of appropriate‐for‐gestational‐age (AGA) pregnancies that were scanned at 18–22 weeks during the study period. AGA was defined as EFW > 10 th percentile and ≤ 89 th percentile. Prenatal and delivery records were reviewed and demographic and outcome variables were collected. Multivariable logistic regression models were applied to assess the impact of LGA diagnosed in the second trimester on the development of GDM and LGA at birth (birth weight ≥ 90 th percentile). Results: The study population included 756 patients with a LGA fetus and 756 with an AGA fetus on second‐trimester ultrasound examination. In patients with a LGA fetus diagnosed during the second‐trimester ultrasound examination, the incidence of GDM was 6.0% and the incidence of LGA at birth was 14.9%. Among patients with a LGA fetus in the second trimester, those who developed GDM or LGA at birth were significantly older and were more likely to be obese. Moreover, parity was associated with neonatal LGA ( P  = 0.0003) but not with GDM ( P  = 0.82). On multivariable logistic regression analysis with adjustment for age, parity, change in gestational body mass index, obesity, ethnicity and neonatal sex, LGA diagnosed during the second trimester was associated significantly with GDM (adjusted odds ratio (aOR), 2.54; 95% CI, 1.29–5.03; P  = 0.007) and LGA at birth (aOR, 6.85; 95% CI, 3.60–13.05; P  < 0.0001). Conclusions: LGA diagnosed during second‐trimester ultrasound examination is associated with the development of GDM and LGA at birth, independent of known risk factors, and could be used to identify these women earlier for intervention. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.